2017
DOI: 10.1038/s41598-017-17538-0
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal Organic Nanoflowers

Abstract: Nano-flowers reported so far were mostly constituted of inorganic or hybrid materials. We have synthesized and crystallized a new organic compound, 1, 2-bis(tritylthio)ethane forming an organic nano-flower consisting of single crystalline petals. Crystal structure at nano and micro level indicates that π-π stacking interactions between aromatic systems is the principal factor governing molecular recognition and assembly. Single crystal X-ray Diffraction (S-XRD) supported by Selective Area Electron Diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…The perfectly aligned crystalline planes within individual nanorods of both BaWO 4 control and BaSrWO 4 solid-solution samples are consistent with their single-crystalline nature. This highly crystalline character of these nanorods was also corroborated by the discrete and well-defined spots, observed in their corresponding SAED patterns (Figure J,K) …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The perfectly aligned crystalline planes within individual nanorods of both BaWO 4 control and BaSrWO 4 solid-solution samples are consistent with their single-crystalline nature. This highly crystalline character of these nanorods was also corroborated by the discrete and well-defined spots, observed in their corresponding SAED patterns (Figure J,K) …”
Section: Resultssupporting
confidence: 68%
“…This highly crystalline character of these nanorods was also corroborated by the discrete and well-defined spots, observed in their corresponding SAED patterns (Figure 2J,K). 29 By contrast, Mn-doping of the tungstate lattice yields a different set of characteristic signatures (Figure 2I,L). Specifically, the d-spacing associated with the (112) facet reduces from 0.331 to 0.321 nm, and this observation is coupled with the appearance of an additional (004) facet characterized by a d-spacing value of 0.313 nm.…”
Section: Morphological Characterization Of Thementioning
confidence: 98%
“…Furthermore, in order to investigate silica distribution, 0.1 wt.% zinc oxide was added to fumed silica NPs. Based on zinc energy dispersive X-ray spectrometry (EDS) mapping 34 , it was found that fumed silica NPs coated clay layers uniformly. In addition, zinc dispersion indicates that this technique of producing hydrothermal CS-NPs is suitable for modified homogenous bitumen blending.…”
Section: Resultsmentioning
confidence: 99%
“…Uvaol 1 containing two hydroxyl groups at the two ends of the molecule along with a 6-6-6-6-6 pentacyclic ursane-type hydrophobic backbone makes it a unique unsymmetrical bola amphiphile for the study of its self-assembly properties in several neat organic liquids and aqueous organic binary liquids. The self-assemblies and flowerlike porous superstructure from metal oxide nanocomposite and inorganic substances in different media have been reported. But the self-assembly of garland and flowerlike porous architectures from triterpene-based amphiphiles and synthesized organic compounds is not common. ,, …”
Section: Introductionmentioning
confidence: 99%